Examining the Mythos. (Economist, 2026)
The article discusses how Anthropic's powerful new A I model, Mythos, is being restricted from public release due to its ability to find critical security flaws, though researchers believe A I hacking tools may ultimately benefit cyber defenders. Topics include the model's superiority in finding zero-day bugs, the guarded optimism of security experts; and the high cost and maintenance challenges of A I-driven bug hunting.